The Role of Auditors in the Digital Society - Sheerazy, Muhammad Muhiyidin Sabith; Svatá, Vlasta, 1952-; Muknšnábl, Josef; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2020)
The topic of my thesis is (the role of auditors in the digital society). The thesis contains eight chapters explaining from chapter one to chapter four the evolution of auditors in the digital society, including the latest frameworks, the importance of information in the current society. In chapter four, the continuous audit is explained how the audit role can be enhanced using tools and technologies and the essential role that it plays in an audit. From chapter 5 to chapter 8 will be explained the organization Company X as an example to show the current process, organization structure and its applicability to enhance its audit function of continuous audit and continuous monitoring. Finally, chapter eight contains the conclusion that concludes my findings from the theoretical part that supports the practical part. The aim of the thesis has been answered, including questions supporting the aim of the thesis has been answered to best suit the auditors in the digital society.
Vedoucí práce: Vlasta Svatá
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses